Infertility Treatment and Traditional Chinese Medicine - Lewis, Taylor Gabrielle (The University of Arizona., 2017)
Infertility treatments are sought after by about one in every ten women in the United States. In vitro fertilization (IVF) and intra-uterine insemination (IUI) are both relatively expensive and time consuming fertility options for patients and yet still cannot guarantee pregnancy will be achieved. Incorporating acupuncture into an IVF cycle creates a sympathoinhibitory effects, decreases pulsatillity index, and promotes increased uterine artery blood flow and therefore increased endometrial thickness and increased likelihood of embryo implantation. Additionally, acupuncture normalizes hypothalamic-pituitary-ovarian axis dysfunction. Incorporating Chinese herbal medicine (CHM) into an IVF cycle promotes estrogenic effects including uterine support through the luteal phase. Incorporating CHM into an IUI regimen helps to alleviate the anti-estrogenic effects of the follicle stimulating pharmaceuticals prescribed. In randomized trials, acupuncture and CHM significantly increased endometrial thickness measurements and CHM significantly increased pregnancy and live birth rates when used alongside IVF. Most patients have negative perceptions regarding traditional Chinese medicine and are therefore not receptive to using it or incorporating it into their fertility treatment plan. Because some positive effects and no negative effects have been found, physicians should continue to recommend these complementary approaches to their patients, provided the addition of TCM is financially feasible for the patient.